Angle-specific analysis of isokinetic quadriceps and hamstring torques and ratios in patients after ACL-reconstruction - Christian Baumgart; Wouter Welling; Matthias W. Hoppe; Jürgen Freiwald; Alli Gokeler (BMC, 2018)
Abstract Background Strength deficits, muscle imbalances, and quadriceps inhibition are common after the surgical reconstruction of the anterior cruciate ligament (ACL), even after the patient's returned-to-sport. Typically, asymmetries between the operated and non-operated leg as well as the hamstring/quadriceps (HQ) ratio are calculated using maximum isokinetic torque values. Moreover, the knee flexion angles, which correspond to the measured torque values, were not considered. Therefore, the aim of the study was to evaluate the usage of an angle-specific approach for the analysis of isokinetic data in patients after an ACL-reconstruction. Methods A cross-sectional laboratory study design was used to investigate the influence of leg (operated vs. non-operated) and two velocities on angle-specific isokinetic data. Concentric quadriceps and hamstring torques and ratios of 38 patients were assessed 6.6 months after ACL-reconstruction with a hamstring tendon graft. At a velocity of 60°/s and 180°/s, angle-specific torques and HQ-ratios were analyzed with conventional discrete parameters and a Statistical Parametric Mapping procedure, which evaluates continuous data. The relationship between angle-specific and conventional HQ-ratios was evaluated with Pearson correlation coefficients. Results Angle-specific torques and HQ-ratios were different between the operated and non-operated leg and between velocities. In the operated leg, the quadriceps deficit was higher at 60°/s in knee flexion angles > 50°. The HQ-ratios decreased with greater knee flexion at both velocities, but with a different magnitude. Around 30°, the HQ-ratios reached 1.0 and did not differ between the velocities, while leg differences were present from 40 to 60°. At the higher testing velocity, the maximum flexion torque occurred at greater knee flexion, whereas the maximum extension torque were present at a similar joint angle. The correlation coefficients between conventional and angle-specific HQ-ratios were low in knee angles < 35° and > 65° and varied according to leg and velocity. Conclusions The angle specific approach is recommended for future ACL-research, as it reveals strength deficits and imbalances, which were not captured by conventional parameters. The results provide a rationale for more specific joint angle and/or velocity based training and may help for return-to-sport decisions.